Acquired combined immunodeficiency associated with protein losing enteropathy complicating Fontan operation. Issue 10 (15th September 2003) - Chakrabarti, S; Keeton, B R; Salmon, A P; Vettukattil, J J
Abstract : It is vitally important that the immunological aspect of protein losing enteropathy following Fontan procedures is highlighted, in order to decrease significant morbidity and mortality